Paralleled multi‐terminal DC transmission line fault locating method based on travelling wave. Issue 12 (1st December 2014) - Cheng, Jingzhou; Guan, Minyuan; Tang, Lv; Huang, Hongyang; Chen, Xin; Xie, Jiajia
Abstract : This study presents a novel protection criterion of fault locating in multi‐terminal DC (MTDC) transmission systems. When a fault occurs on the DC transmission line of the MTDC system, the traditional protection cannot locate the fault because there is no smoothing reactor (equipped at the converter output) in the transmission lines. In the circumstance of AC/DC conductor contact (ADCC) fault, the varieties of the transient voltage and current components are given based on the symmetrical fault analysis. According to the Bergeron equation, the travelling wave characteristic is analysed. A new criterion of fault locating using the change rate of the current travelling wave is presented which can reduce the impacts of the related fault on the AC system. Finally, simulation results verify the effectiveness of the proposed protection criterion.